Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.22161/ijaers.79.29
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pequi Residual Biomass from the Brazilian cerrado for obtaining raw and activated biochars and bio-oil

Abstract: The pequi (Caryocar brasiliense Camb) is a fruit native to the Cerrado, with a production of 765 tons per year. However, their peels (76% of the fruit) are generally discarded. In this study, the physical-chemical characterization of the biomass of the pequi was carried out and physical activation processes were developed through slow pyrolysis and physical chemical activation with zinc chloride (ZnCl2) to produce bio-based products, including bio-oil (30.5%) and biochar (34%). Analytical techniques, such as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Acid hydrolysis of cupuaçu husks produced a satisfactory flavoring in the production of vanilla, bacon, ham, whiskey, and rums and currently recognized for its anti-inflammatory potential (Zhao et al, 2019). Brito et al (2020) verified the predominant presence of vaccenic acid (21.2%), palmitic acid (19.7%), and furfural (7%) compounds in bio-oil derived from pequi residual biomass. Rambo et al (2021), like this study, identified guaiacol (28.7%) and creosol (22.5%) compounds in bio-oil derived from baru hydrolyzed endocarp.…”
Section: Discussionmentioning
confidence: 89%
“…Acid hydrolysis of cupuaçu husks produced a satisfactory flavoring in the production of vanilla, bacon, ham, whiskey, and rums and currently recognized for its anti-inflammatory potential (Zhao et al, 2019). Brito et al (2020) verified the predominant presence of vaccenic acid (21.2%), palmitic acid (19.7%), and furfural (7%) compounds in bio-oil derived from pequi residual biomass. Rambo et al (2021), like this study, identified guaiacol (28.7%) and creosol (22.5%) compounds in bio-oil derived from baru hydrolyzed endocarp.…”
Section: Discussionmentioning
confidence: 89%
“…In our previous studies, Brito et al, (2020), the activated biochar of the pequi peel was characterized and the results are shown in Table 1. Through Table 1, we can observe the characterization of the Pequi bark.…”
Section: Characterization Of Biochar From Pequi Peelmentioning
confidence: 99%